Hot air balloon being inflated on Front Street, Dawson, Yukon Territory, ca. 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.133 [Meed journal: "A hot-air balloon ascent and parachute descent inflated on Front Street, Dawson. The performer was rescued from the river."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number